Protein Stability and Dynamics Modulation: The Case of Human Frataxin - Roman, E.A. (2012)
Frataxin (FXN) is an α/β protein that plays an essential role in iron homeostasis. Apparently, the function of human FXN (hFXN) depends on the cooperative formation of crucial interactions between helix α1, helix α2, and the C-terminal region (CTR) of the protein. In this work we quantitatively explore these relationships using a purified recombinant fragment hFXN90-195. This variant shows the hydrodynamic behavior expected for a monomeric globular domain. Circular dichroism, fluorescence, and NMR spectroscopies show that hFXN90-195 presents native-like secondary and tertiary structure. However, chemical and temperature induced denaturation show that CTR truncation significantly destabilizes the overall hFXN fold. Accordingly, limited proteolysis experiments suggest that the native-state dynamics of hFXN90-195 and hFXN90-210 are indeed different, being the former form much more sensitive to the protease at specific sites. The overall folding dynamics of hFXN fold was further explored with structure-based protein folding simulations. These suggest that the native ensemble of hFXN can be decomposed in at least two substates, one with consolidation of the CTR and the other without consolidation of the CTR. Explicit-solvent all atom simulations identify some of the proteolytic target sites as flexible regions of the protein. We propose that the local unfolding of CTR may be a critical step for the global unfolding of hFXN, and that modulation of the CTR interactions may strongly affect hFXN physiological function. © 2012 Roman et al.